Potensi Tanaman Sumber Pakan pada Budidaya Lebah Madu (Apis cerana F.) di Hutan Pendidikan Wanagama I, Gunungkidul - Dewi Anita; Musyafa Musyafa; Siti Muslimah Widyastuti (Faculty of Forestry Universitas Gadjah Mada, 2022)
Apis cerana became a common species for beekeeping activities in Indonesia. The sustainability of beekeeping activities depended on the availability of feeds in forests with various plant species, which served as honey bee forage. Therefore, this study aimed to determine the forage plant diversity for A. cerana beekeeping in Wanagama Education Forest, Gunungkidul, from November 2018 to April 2019. Data collection was done through the inventory of trees and understorey plant species around the apiary locations to measure their abundance, flowering conditions, and the number of honey bees on the flower. The analysis indicated that 20 species (10 families) of trees and 60 species (19 families) of understorey plants had potential forage. The observation revealed that honey bees collected nectar and pollen from seven species of trees and 12 species of understorey plants. The highest visitation intensity was in the morning from two trees (Acacia mangium and Eucalyptus grandis) and three understoreys (Oxalis barrelieri, Passiflora suberosa, and Zea mays). Information on potential plant species for honey bee forage could improve beekeeping development in Wanagama Education Forest.